DETERMINATION OF MINIMAL DEPRESSIVE CONCENTRATION OF ESSENTIAL OIL OF MONARDA FISTULESA TOWARDS FUNGI CULTURE OF ASPERGILLUS FUMIGATUS - Polyanskaya, V.P.; Kynashiv, A.V.; Kovalenko, N.P.; Sarhosh, A.V. (World of Medicine and Biology, 2015)
The use of essential oils as natural concentrates of phytoncides is a promising way to fight pathogenic microorganisms. Their content includes over 300 components that determine a wide range of pharmacological properties such as antimicrobial, antibacterial, antiviral, anti-inflammatory and immune-modulative. Recently researchers have paid special attention to essential oil of Mornadafistulesa. It is known for its antimicrobial properties against Streptococcus pyogenes, Neisseria catarralis and Candida albicans. Though, its antifungal properties towards Mycelium fungi need further studies. The research is aimed to determine the minimal fungistatic and fungicidal concentrations of the essential oil of Monardafistulesa towards culture of Aspergillusfumigatus because inhalation of Aspergillus spp. spores while breathing may cause respiratory diseases in humans and animals. It has been determined that essential oil ofMonardafistulesa has strong fungicidal properties towards the culture of Aspergillusfumigatus. The minimal depressive concentration of the essential oil after 24 and 72 hours of incubation was 29.2 mg/ml. Prolonged exposure of Aspergillusfumigatus to the essential oil of Monardafistulesa shows that the fungicidal properties of the essential oil are increased. Thus, the essential oil of Monardafistulesamay be used as an antifungal substance.
Keywords: essential oil; Monarda fistulosa; fungi species Aspergillus fumigatus; concentration